Chemical elements in the environment: Multi-element geochemical datasets from continental- to national-scale surveys on four continents. (February 2018) - Caritat, P. de; Reimann, C.; Smith, D.B.; Wang, X.
Abstract: During the last 10–20 years, Geological Surveys around the world have undertaken a major effort towards delivering fully harmonised and tightly quality controlled low-density multi-element soil geochemical maps and datasets of vast regions including up to whole continents. Concentrations of between 45 and 60 elements commonly have been determined in a variety of different regolith types (e.g., sediment, soil). The multi-element datasets are published as complete geochemical atlases and made available to the general public. Several other geochemical datasets covering smaller areas, but generally at a higher spatial density, are also available. These datasets may, however, not be found by superficial internet-based searches because the elements are not mentioned individually either in the title or in the keyword lists of the original references. This publication attempts to increase the visibility and discoverability of these fundamental background datasets covering large areas up to whole continents. Highlights: Up to 60 elements analysed in thousands of soil samples covering 4 continents. Provide unique empirical data on geochemical context of soils on Earth. Essential to refer to global/continental context when studying chemical cycles. Original datasets and reports suffer from poor discoverability by internet searches. This paper aims to increase visibility and awareness of datasets among researchers.